2020
DOI: 10.1590/1807-2577.07320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whitening dentifrices containing optical agent on the variation of color, roughness and mass of a nanoparticulate composite resin

Abstract: Introduction Blue covarine is a pigment that promotes optical changes in dental surfaces, providing whitening. Objective To evaluate in vitro the effect of bleaching dentifrices containing Blue covarine in nanoparticulate composite resin subjected to artificial darkening. Material and method One hundred sixty (160) specimens (PBs) of FILTEK Z350XT nanoparticulate composite resin were randomly divided into two experiments: Experiment I - 8 groups (n=10) submitted to brushing with an electric toothbrush for 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…12,15,16,18 Previous studies have reported different results of whitening toothpastes on composite resins in terms of surface roughness. [14][15][16][17][18][19][20][21] However, only one of the cited studies used the same 2 kinds of toothpaste used in this study. 21 In addition, some of the studies did not provide information about the toothpastes compositions they used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,15,16,18 Previous studies have reported different results of whitening toothpastes on composite resins in terms of surface roughness. [14][15][16][17][18][19][20][21] However, only one of the cited studies used the same 2 kinds of toothpaste used in this study. 21 In addition, some of the studies did not provide information about the toothpastes compositions they used.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IWL contains mica, known as an abrasive agent. 20 Mica may have been effective in increasing the surface roughness of composite resins after toothbrushing with IWL. It has been stated that not only abrasives but also detergents in toothpastes can cause dental wear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation